A study of bacterial vaginosis in HUSM- toward a standard :diagnostic method - Hussin, Azura (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
The diagnosis of Bacterial Vaginosis (BV) is commonly established by using the Amsel's criteria, which is based mainly on clinical presentation. However, BV was often under diagnosed when the clinical criteria are used because of its inherent subjectivity. A more objective method like the Nugent's criteria is more reliable especially in asymptomatic patients. This study Is perfonned to study the prevalence of BV among pregnant women In HUSM and to evaluate its accuracy comparing to the standard Amsel's criteria. Methodology: A cross sectional study was randomly conducted among pregnant women, attending Obstetric and Gynaecology Clinic in HUSM for six months duration. The prevalence of BV was determined by the Amsel's and Nugent's criteria. The agreement of the two criteria was observed and the validity of the Nugent's criteria was evaluated using the Amsel's criteria as gold standard. Results: 270 patients were recruited into the study. The prevalence of bacterial vaginosis using the Amsel's criteria was 1.0 % (95% Cl) and 2.6% (95% Cl) by Nugent's criteria. The sensitivity, specificity, positive predictive value and negative predictive value of the Nugent's criteria, using the Amsel's criteria as gold standard was 100%, 98.5%, 42.9% and 100%, respectively, with moderate agreement between the two criteria (k=0.594 and p=<0.001 ). Conclusion: The prevalence of BV among pregnant women in HUSM by using the Amsel's criteria ts slightly tower (1.0%) compared to the Nugent's criteria (2.6%). Both criteria could be used to diagnose BV, however Nugent's criteria is more standardized, objective and simple to perfonn, thus more suitable especially for research purpose.